Energy Planning in Selected European Regions - Methods for Evaluating the Potential of Renewable Energy Sources - Sliz-Szkliniarz, Beata (Regionalwissenschaftliche Forschungen = Regional Science Research, 2013)
Given their potentially positive impact on climate protection and the preservation of fossil resources, alternative energy sources have become increasingly important for the energy supply over the past years. However, the questions arises what economic and ecological impacts and potential conflicts over land use resources are associated with the promotion of renewable energy production. Using the examples of three selected European Regions in Poland, France and German, the dissertation discusses these questions and examines the potential and consequences of an intensified usage of renewable energy sources.